2019
DOI: 10.3390/jcm8122057
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Level Classification System: Usefulness in Patients with Liver Cirrhosis

Abstract: Currently, the Japanese society of clinical nutrition (JSCN) defines serum zinc (Zn) level < 60 μg/dL as Zn deficiency and 60 μg/dL ≤ serum Zn level < 80 μg/dL as subclinical Zn deficiency, and 80 μg/dL ≤ serum Zn level < 130 μg/dL as normal Zn range. We aimed to elucidate the prognostic impact of this Zn classification system in patients with liver cirrhosis (LC) compared to the Child–Pugh classification and the albumin–bilirubin (ALBI) grading system (n = 441, median age = 66 years). The Akaike info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…In our previous study, we reported that the serum Zn level grading system proposed by JSCN seems to be helpful for estimating OS in LC patients [31]. In the current results, the serum Zn level grading system proposed by JSCN had the lowest AIC value among the three prognostic models for the incidence of Com-HEs in all cases and in several subgroups.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…In our previous study, we reported that the serum Zn level grading system proposed by JSCN seems to be helpful for estimating OS in LC patients [31]. In the current results, the serum Zn level grading system proposed by JSCN had the lowest AIC value among the three prognostic models for the incidence of Com-HEs in all cases and in several subgroups.…”
Section: Discussionsupporting
confidence: 45%
“…As mentioned in the introduction section, JSCN defines Zn deficiency, subclinical Zn deficiency, and a normal Zn value based on the serum Zn level [31]. However, the predictability of the serum Zn level grading system in HCV-related LC patients on the incidence of Com-HEs has not been fully investigated, which motivated us to perform the current analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Figure 2A) The median (IQR) serum Zn level in patients with npRQ < 0.85 (n = 242, 58 µg/dL (47, 66.25 µg/dL)) was significantly lower than that in patients with npRQ ≥ 0.85 (n = 344, 68 µg/dL (61, 75 µg/dL)) (p < 0.0001). ( Figure 2B) Currently, the Japanese society of clinical nutrition (JSCN) defines the followings: (A) serum Zn level <60 µg/dL corresponds to Zn deficiency; (B) 60 µg/dL ≤ serum Zn level < 80 µg/dL corresponds to subclinical Zn deficiency; and (C) 80 µg/dL ≤ serum Zn level < 130 µg/dL corresponds to normal Zn level [33]. The median npRQ levels in patients with Zn deficiency (n = 211), subclinical Zn deficiency (n = 305) and normal Zn range (n = 70) were: 0.82 (0.78, 0.86), 0.88 (0.84, 0.95) and 0.94 (0.8375, 1.01) (p < values: Zn deficiency versus subclinical Zn deficiency, p < 0.0001; subclinical Zn deficiency versus normal Zn level, p = 0.0038; Zn deficiency versus normal Zn level, p < 0.0001; overall p < 0.0001) ( Figure 2C).…”
Section: Correlation Between Nprq Level and Serum Zn Level For All Casesmentioning
confidence: 99%